Problemy konstruowania motywacyjnych tabel płac w firmach sektora MŚP - na przykładzie firmy projektowej - Tracz, Ewa (Problems of building motivating payment tables in SME sector - a project firm case, 2007)
The article describes general rules and tendencies in building motivating payment tables, an example of the table and assumptions behind its development, based on the case of a firm from SME sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 234-242